TP53 Genotype but Not p53 Immunohistochemical Result Predicts Response to Preoperative Short-Term Radiotherapy in Rectal Cancer - Kandioler, Daniela (2002)
OBJECTIVE: To evaluate and compare the predictive power of p53 gene analysis versus p53 immunohistochemical staining in terms of response to preoperative short-term radiotherapy using 25 Gy in operable rectal cancer. SUMMARY BACKGROUND DATA: Recent studies show that p53 may be a determinant of radiosensitivity being required for induction of apoptosis in case of radiation-induced DNA damage. METHODS: Preirradiation biopsy samples of 64 patients with rectal carcinoma were analyzed. Genetic alterations of the p53 gene were detected by complete direct sequencing of exons 2 to 10. Expression of the nuclear phosphoprotein p53 was assessed by immunohistochemical staining. Results were correlated with histopathology of resected specimens and follow-up data, respectively. RESULTS: Mutations of the p53 gene were present in 45% of tumors. Patients with a normal p53 gene had a significant survival advantage. Comparing pre- and postradiotherapy T category, a reduction was seen in patients with normal p53 genotype only. A mutant p53 genotype was highly specific in indicating stable disease concerning T category after irradiation. Protein overexpression was detected in 61%. Overexpression of the p53 protein was not related to survival or response. The concordance between immunohistochemistry and sequencing was only 0.51. CONCLUSIONS: The authors show that downstaging after short-term radiation may occur but is seen in tumors with normal p53 gene only. Moreover, p53 genotype but not p53 immunohistochemistry is predictive for response to preoperative short-term radiotherapy and patient survival.